Two short implants versus one short implant with a cantilever: 5‐Year results of a randomized clinical trial. (22nd September 2021) - Thoma, Daniel S.; Wolleb, Karin; Schellenberg, Roman; Strauss, Franz‐Josef; Hämmerle, Christoph H. F.; Jung, Ronald E.
Abstract: Aim: To test whether or not the use of a short implant with a cantilever results in similar clinical and radiographic outcomes compared to two adjacent short implants with single tooth reconstructions. Materials and methods: Thirty‐six patients with two adjacent missing teeth in the posterior region were randomly assigned to receive either a single 6‐mm implant with a cantilever (ONE‐C) or two 6‐mm implants (TWO). Fixed reconstructions were inserted 3–6 months after implant placement and patients were re‐examined up to 5 years (FU‐5). Results: A total of 26 patients were available for re‐examination at FU‐5. The survival rate amounted to 84.2% in ONE‐C and to 80.4% in TWO (inter‐group: p = .894). Technical complication rates amounted to 64.2% (ONE‐C) and to 54.4% (TWO) (inter‐group: p = 1.000). From baseline to FU‐5, the median changes of the marginal bone levels were 0.13 mm in ONE‐C and 0.05 mm in TWO (inter‐group: p = .775). Probing depth, bleeding on probing, and plaque control record values showed no significant differences between the two treatment modalities ( p > .05). Conclusions: Short implants with a cantilever render similar clinical and radiographic outcomes compared to two adjacent short implants at 5 years, however, they tend to fail at earlier time points suggesting an overload of the implants. Considering the modest survival rates, the clinical indication of either treatment option needs to be carefully evaluated. ClinicalTrials.gov (NCT01649531).